Labor Flexibility in Multiechelon Dual-Constraint Job Shops - Frye, John S. (Management Science, 1974)
In this paper a simulation study of the effects of labor flexibility on the performance of a multiechelon dual-constraint job shop is described. Machines and workers are constraining resources in the hypothetical shop. The organizational structure of the shop consists of divisions comprised of work centers that contain machines and workers. There are fewer workers than machines. Independent variables are interdivisional and intradivisional labor flexibility. Mean flow-time, flow-time variance and worker transfers between divisions and work centers are used as measures of shop performance. Labor flexibility is shown to have a major effect on shop performance. The effectiveness of interdivisional labor flexibility as a management variable is found to be concentrated in the region of high flexibility while intradivisional labor flexibility is most effective in the region of low flexibility.